2013
DOI: 10.5588/ijtld.11.0831
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of HAART in tuberculosis-HIV co-infected patients in Brazil

Abstract: SUMMARY BACKGROUND Antiretroviral therapy (ART) significantly reduces tuberculosis (TB) incidence among persons with human immunodeficiency virus (HIV), but the safety and effectiveness of concomitant treatment for both diseases remain unclear. OBJECTIVE To evaluate the impact of ART and anti-tuberculosis treatment on survival and risk of adverse events (AE) among co-infected individuals. METHODS In a retrospective cohort study, clinical data were collected from 618 TB-HIV patients treated with rifampin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Studies reported more PTB- cases among HIV-infected individuals [36] , [46] , while previous studies from southern Ethiopia also reported a high TB-HIV co-infection, with the rate of HIV infection among PTB- cases being 18–26% [36] , [37] . The declining trend in mortality during treatment in our study may be explained in part by ART services because ART reduces deaths in TB cases infected with HIV [47] . In recent years, there has been an increase in both ART centers and the number of patients starting ART in the study area [24] .The number of ART centers in the study area increased from one to 20 during the study period.…”
Section: Discussionmentioning
confidence: 71%
“…Studies reported more PTB- cases among HIV-infected individuals [36] , [46] , while previous studies from southern Ethiopia also reported a high TB-HIV co-infection, with the rate of HIV infection among PTB- cases being 18–26% [36] , [37] . The declining trend in mortality during treatment in our study may be explained in part by ART services because ART reduces deaths in TB cases infected with HIV [47] . In recent years, there has been an increase in both ART centers and the number of patients starting ART in the study area [24] .The number of ART centers in the study area increased from one to 20 during the study period.…”
Section: Discussionmentioning
confidence: 71%
“…The characteristics of the included studies are reported in Table 1 . The majority of the studies were conducted in the African (n = 11, 52%) [14] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] and South-East Asian (n = 7, 33%) [33] , [34] , [35] , [36] , [37] , [38] , [39] regions; two studies were conducted in South America [40] , [41] and one in Europe [42] . Four out of seven studies in the South-East Asian region were conducted in Thailand [33] , [35] , [37] , [38] while one used data from eighteen sites in the Asia-Pacific region [39] .…”
Section: Resultsmentioning
confidence: 99%
“…The main interactions are between the anti-TB drugs rifampicin and rifabutin and antiretroviral drugs, in particular PIs (Baciewicz, Chrisman, Finch, & Self, 2008). Patients on combined treatment have an increased risk of adverse events (Dos Santos et al, 2013;Dean et al, 2002).…”
Section: Treatment Challengesmentioning
confidence: 99%
“…In the current Swedish national guidelines for HIV treatment, PI-based cART is a recommended first-line alternative after the NNRTI efavirenz, in combination with anti-TB treatment (Referensgruppen för antiviral terapi, 2014). The most common cART in the study setting was PI-based, which has been associated with a higher risk of adverse reactions than efavirenz-based cART (Dos Santos et al, 2013).…”
Section: Hiv-related Tb In the Study Settingmentioning
confidence: 99%